Distinct orthography boosts morphophonological discrimination: vowel raising in Bengali verb inflections - Althaus, N; Kotzor, S; Schuster, S; Lahiri, A (Elsevier, 2022)
This study is concerned with how vowel alternation, in combination with and without orthographic reflection of the vowel change, affects lexical access and the discrimination of morphologically related forms. Bengali inflected verb forms provide an ideal test case, since present tense verb forms undergo phonologically conditioned, predictable vowel raising. The mid-to-high alternations, but not the low-to-mid ones, are represented in the orthography. This results in three different cases: items with no change (NoDiff), items with a phonological change not represented in the orthography (PronDiff) and items for which both phonology and orthography change (OrthPronDiff).